Transforming Kafka : translation effects - O'Neill, Patrick, 1945- (German and European studies., 2014)
Lyrical, mysterious, and laden with symbolism, Franz Kafka's novels and stories have been translated into more than forty languages ranging from Icelandic to Japanese. In Transforming Kafka, Patrick O'Neill approaches these texts through the method he pioneered in Polyglot Joyce and Impossible Joyce, considering the many translations of each work as a single, multilingual macrotext. Examining three novels -- The Trial, The Castle, and America -- and two short stories -- The Judgment and The Metamorphosis -- O'Neill offers comparative readings that consider both intertextual and intratextual themes. His innovative approach shows how comparing translations extends and expands the potential meanings of the text and reveals the subtle differences among the hundreds of translations of Kafka's work. A sophisticated analysis of the ways in which translation shapes, rearranges, and expands our understanding of literary works, Transforming Kafka is a unique approach to reading the works of a literary giant. -- From publisher's website.